Disinfection of dental impressions: knowledge and practice among dental technicians - Al Mortadi N; Al-Khatib A; Alzoubi KH; Khabour OF (Dove Medical Press, 2019)
Noor Al Mortadi,1 Aceil Al-Khatib,2 Karem H Alzoubi,3 Omar F Khabour41Department of Applied Dental Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Oral Medicine and Oral Surgery, Faculty of Dentistry, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, Jordan; 4Department of Medical laboratory Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, JordanBackground: Dental impressions are a common source for transmission of infection between dental clinics and dental labs. Dental impressions can be cross-contaminated by patient’s saliva and blood, which then cross-infect the dental casts poured from the impressions.Objective: To evaluate the current practices of disinfection of dental impressions and their protocols and to assess the knowledge of cross-infection control among dental technicians in Jordan.Method: Dental technicians (n=85) completed a self-administered questionnaire about their practices of disinfection for dental impressions.Results: The distribution of dental technicians was 63.8% fixed prosthodontics, 23.5% removable prosthodontics, 7.8% orthodontics, and 4.8% maxillofacial prosthodontics. The majority of the laboratories did not have instructions related to disinfection of impressions. About 50% of technicians were vaccinated against HBV. About 44.7%, and 42.9% of labs reported that they never disinfect alginate or silicon impressions, respectively. In addition, the majority of lab owners (53%) believed that the dentist should disinfect the impressions before shipping them to dental laboratories, while (45%) believed that disinfecting the impressions is the responsibility of the dental assistant. Moreover, about 38% of this study population reported not using gloves in their labs. In those labs were disinfection was used, 51% used spray disinfection whereas 32.6% used immersion disinfection. The cost of disinfectant was ranked as the most important factor (51.3% of the cases) for the dental technician to choose the disinfectant followed by its effectiveness.Conclusion: Dental technician practices in impression disinfection was not satisfactory, therefore, education programs about impression disinfection are needed.Keywords: disinfection, dental impressions, knowledge, practice, dental technicians